Effects of full-length human amelogenin on the differentiation of dental epithelial cells and osteoblastic cells. (November 2019) - Takahashi, Ayumi; Morita, Takao; Murata, Kaori; Minowa, Erika; Jahan, Azmeree; Saito, Masato; Tanimura, Akihiko
Highlights: Differentiation of HAT-7 cells was enhanced by full-length recombinant human amelogenin (rh-AMEL) at high concentration, but not by Emdogain®. Differentiation of MC3T3-E1 cells was enhanced by rh-AMEL at low concentrations, but was strongly reduced at high concentration. The effects of Emdogain® on MC3T3-E1 cells were similar to those of rh-AMEL. The biphasic effect of rh-AMEL on MC3T3-E1 cells may be related to the prevention of ankylosis during the development of tooth roots. Abstract: Background and objective: Amelogenins are major components of extracellular matrix proteins in developing teeth, and regulate the growth of enamel crystals. They also function as signaling molecules in cell differentiation. This study aimed to determine the biological effects of amelogenins on the differentiation of HAT-7 dental epithelial cells and MC3T3-E1 pre-osteoblastic cells using full-length recombinant human amelogenin (rh-AMEL). Design: rh-AMEL was expressed in a mammalian cell line (Expi293F™) and was purified by DDK agarose beads. Effects of rh-AMEL on differentiation were evaluated by Mineralization and Alkaline phosphatase (ALP) activity using Alizarin Red S staining and colorimetric substrate p-nitrophenol, respectively. Results: Western blotting and silver staining confirmed the successful purification of rh-AMEL. Mineralization and ALP activity in HAT-7 cells were significantly higher after treatment with 4 μg/mL rh-AMEL, but not after treatment with Emdogain ® (EMD). In MC3T3-E1 cells, on the other hand, rh-AMEL showed biphasic effects on differentiation. Treatment with low concentrations of rh-AMEL (0.001–0.1 μg/mL) and EMD (0.01–1 μg/mL) increased mineralization and ALP activity in MC3T3-E1 cells, whereas treatment with high concentrations of rh-AMEL (4 μg/mL) and EMD (100 μg/mL) had the opposite effect. Conclusion: High concentrations of rh-AMEL and EMD decreased the differentiation of MC3T3-E1 cells. By contrast, a high concentration of rh-AMEL, but not that of EMD, promoted the differentiation of HAT-7 cells. This study demonstrates that the effects of rh-AMEL on cell differentiation differ between HAT-7 and MC3T3-E1 cells, and suggests that different regions on AMEL may induce the differentiation of these cell types.